The Influence of Trust on Consumer Purchasing Decisions for Local SME Products: A Comparison of Sales Through E-Commerce and Offline Stores with an Experimental Approach - Basri Basir MR; Fitriany; Andi Ririn Oktaviani (LP2M IAIN Palopo, 2026)
The Influence of Trust on Consumer Purchasing Decisions for Local SME Products: Comparison of Sales via E-Commerce and Offline Stores with an Experimental Approach, guided by Fitriany and Andi Ririn Oktaviani. This study examines the extent to which trust influences consumer purchasing decisions for local MSME products in Makassar City, by comparing two main channels: e-commerce and offline stores. The approach used was quantitative, through a survey of 200 purposively selected respondents. Data analysis was conducted using simple linear regression and validity and reliability tests. The results show that trust plays a significant role in driving purchasing decisions, both online and offline. However, the influence of trust is stronger in the e-commerce context, as indicated by a higher coefficient of determination and significance level. In conclusion, building trust is key for MSMEs, especially in the digital marketplace. Businesses are advised to focus on improving product quality, transaction security, and information transparency to strengthen consumer loyalty on online platforms